2015
DOI: 10.14214/sf.1403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of site-preparation on soil-surface CO<sub>2</sub> fluxes and litter decomposition in a clear-cut in Sweden

Abstract: Impact of site-preparation on soil-surface CO 2 fluxes and litter decomposition in a clear-cut in Sweden Mjöfors K., Strömgren M., Nohrstedt H.-Ö., Gärdenäs A.I. (2015). Impact of site-preparation on soil-surface CO 2 fluxes and litter decomposition in a clear-cut in Sweden. Silva Fennica vol. 49 no. 5 article id 1403. 20 p. Highlights • Disturbances of the soil did not lead to higher CO 2 emissions from the soil. • Heavy mixing of the soil lead to lower CO 2 emissions from the soil. • Buried needles and coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
(71 reference statements)
0
24
0
Order By: Relevance
“…This top layer seemed to have similar C mineralization rates as the underlying humus layer ( Figure 5). In a study conducted 1-2 years after stump harvesting, Mjöfors et al (2015) observed higher CO2 fluxes from the plots with double humus layer than from the control plots with an undisturbed humus layer. However, during the second year, the soil CO2 fluxes from the plots with a double humus layer decreased and equaled those from control plots (Mjöfors et al, 2015).…”
Section: How Stump Harvesting Affects Soil C and N Mineralization Ratmentioning
confidence: 94%
See 2 more Smart Citations
“…This top layer seemed to have similar C mineralization rates as the underlying humus layer ( Figure 5). In a study conducted 1-2 years after stump harvesting, Mjöfors et al (2015) observed higher CO2 fluxes from the plots with double humus layer than from the control plots with an undisturbed humus layer. However, during the second year, the soil CO2 fluxes from the plots with a double humus layer decreased and equaled those from control plots (Mjöfors et al, 2015).…”
Section: How Stump Harvesting Affects Soil C and N Mineralization Ratmentioning
confidence: 94%
“…In a study conducted 1-2 years after stump harvesting, Mjöfors et al (2015) observed higher CO2 fluxes from the plots with double humus layer than from the control plots with an undisturbed humus layer. However, during the second year, the soil CO2 fluxes from the plots with a double humus layer decreased and equaled those from control plots (Mjöfors et al, 2015). Thus, Mjöfors et al (2015) concluded that although mixing favors decomposition it does not necessarily lead to higher CO2emissions from the whole profile, but rather creates SOM cohorts in various soil depths, which then decompose at different rates.…”
Section: How Stump Harvesting Affects Soil C and N Mineralization Ratmentioning
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, field 388 studies on CO2 fluxes in 11-12 year-old stands after stump harvesting are lacking, but studies 389 on 1-2 year-old clear-cuts show that CO2 fluxes from mounds, despite the addition of a top 390 layer, can be lower than those from undisturbed soil . In 391 another study, Mjöfors et al (2015) noted that CO2 fluxes from plots with double humus 392 layer (DHL) were initially higher than from control plots with an undisturbed humus layer. 393…”
mentioning
confidence: 99%
“…A possible reason for the occasionally very low fluxes from DHL 395 plots is that high moisture levels in layers containing much of the OM may have suppressed 396 decomposition and/or gas fluxes (Mjöfors et al, 2015). 397 398…”
mentioning
confidence: 99%